Gender Differences in Cardiogenic Shock Patients: Clinical Features, Risk Prediction, and Outcomes in a Hub Center - Lozano-Jiménez, Sara; Iranzo-Valero, Reyes; Segovia-Cubero, Javier; Gómez-Bueno, Manuel; Rivas-Lasarte, Mercedes; Mitroi, Cristina; Escudier-Villa, Juan Manuel; Oteo-Dominguez, Juan Francisco; Vieitez-Florez, Jose María; Villar-García, Susana; Hernández-Pérez, Francisco José (Frontiers in Cardiovascular Medicine, 2022)
Introduction There is scarce knowledge about gender differences in clinical presentation, management, use of risk stratification tools and prognosis in cardiogenic shock (CS) patients. Purpose The primary endpoint was to investigate the differences in characteristics, management, and in-hospital mortality according to gender in a cohort of CS patients admitted to a tertiary hub center. The secondary endpoint was to evaluate the prognostic performance of the Society of Cardiovascular Angiography and Interventions (SCAI) classification in predicting in-hospital mortality according to sex. Methods This is a retrospective single-Center cohort study of CS patients treated by a multidisciplinary shock team between September 2014 and December 2020. Baseline characteristics and clinical outcomes according to gender were registered. Discrimination of SCAI classification was assessed using the area under the receiver operating characteristic curve (AUC). Results Overall, 163 patients were included, 39 of them female (24%). Mean age of the overall cohort was 55 years (44–62), similar between groups. Compared with men, women were less likely to be smokers and the prevalence of COPD and diabetes mellitus was significantly lower in this group (p < 0.05). Postcardiotomy (44 vs. 31%) and fulminant myocarditis (13 vs. 2%) were more frequent etiologies in females than in males (p = 0.01), whereas acute myocardial infarction was less common among females (13 vs. 33%). Regarding management, the use of temporary mechanical circulatory support, mechanical ventilation, or renal replacement therapy was frequent and no different between the groups (88, 87, and 49%, respectively, in females vs. 42, 91, and 41% in males, p > 0.05). In-hospital survival in the overall cohort was 53%, without differences between groups (52% in females vs. 55% in males, p = 0.76). Most of the patients (60.7%) were in SCAIE at presentation without differences between sexes. The SCAI classification showed a moderate ability for predicting in-hospital mortality (overall, AUC: 0.653, 95% CI 0.582–0.725). The AUC was 0.636 for women (95% CI 0.491–0.780) and 0.658 for men (95% CI 0.575–0.740). Conclusions Only one in four of patients treated at a dedicated CS team were female. This may reflect differences in prevalence of severe heart disease at young (<65) ages, although a patient-selection bias cannot be ruled out. In this very high-risk CS population of multiple etiologies, overall, in-hospital survival was slightly above 50% and showed no differences between sexes. Treatment approaches, procedures, and SCAI risk stratification performance did not show gender disparities among treated patients.